2018
DOI: 10.1176/appi.ps.201700165
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Neighborhood Factors and Community Stigma in Predicting Community Participation Among Persons With Psychiatric Disabilities

Abstract: Findings suggest that effects of neighborhood characteristics and community stigma on people with psychiatric disabilities are complex and are partly conditioned by housing context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 30 publications
2
18
1
Order By: Relevance
“…The preference for social distance from people with mental illness leads to social isolation, loneliness, impaired social networks [ 37 ], and reduced social capital [ 38 ] and community participation. This particularly affects people living with severe mental illness [ 39 , 40 ]. At the same time, people with severe mental illness are at risk of targeted violence and hostility, such as verbal and physical abuse, and sexual and financial exploitation [ 41 ].…”
Section: The Impacts Of Stigma and Discriminationmentioning
confidence: 99%
“…The preference for social distance from people with mental illness leads to social isolation, loneliness, impaired social networks [ 37 ], and reduced social capital [ 38 ] and community participation. This particularly affects people living with severe mental illness [ 39 , 40 ]. At the same time, people with severe mental illness are at risk of targeted violence and hostility, such as verbal and physical abuse, and sexual and financial exploitation [ 41 ].…”
Section: The Impacts Of Stigma and Discriminationmentioning
confidence: 99%
“…Six included empirical studies were qualitative in nature, using focus group (Gonzales et al ., 2015 a ; Peters et al ., 2016), one-to-one semi-structured interviews (Holley et al ., 2016 a ; McCue, 2016; Harper et al ., 2017) and analysis of free-text survey questions (Charles et al ., 2017). Four were cross-sectional surveys (Zurick, 2016; DeLuca et al ., 2017; DeLuca et al ., 2018; Gonzales et al ., 2018), with sample sizes from 222 to 951 participants. Four of these studies employed convenience sampling of the US public using online survey platforms.…”
Section: Resultsmentioning
confidence: 99%
“…The latter was used in three studies aiming to identify individual characteristics associated with endorsement of mental health microaggressions by the general public. Broadly, endorsement of microaggressions was positively associated with right-wing political views (DeLuca et al ., 2018), suburban values and socio-economic disadvantage (Gonzales et al ., 2018), authoritarianism (the attitude that people with serious mental illness cannot care for themselves and require coercion) and social restrictiveness (the belief that people with mental illness should be feared and excluded) (Zurick, 2016). Endorsement was negatively associated with benevolence (the belief that people with mental illness are innocent and naïve) (Zurick, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that other area characteristics, not measured in the current study, could account for the associations we observed. For example, research suggests geographic variation exists in gender norms, beliefs which condone domestic violence, [33][34][35] and stigmatising attitudes towards people with mental illness; 36,37 neighbourhood patterns in violence towards people with mental illness observed in this study could reflect regional differences in attitudes. Material deprivation in neighbourhoods is associated with the experience of violence, across a range of indicators, including intimate partner violence, 38 homicide 39 and use of hospital care for assault.…”
Section: Explanation Of Findingsmentioning
confidence: 88%